Hubungan Interpersonal Skill Karyawan terhadap Minat Masyarakat Muslim Menjadi Anggota Koperasi Syari’ah - Fernandes, Sisco; Hardiizon, H (AL-FALAH : Journal of Islamic Economics, 2016)
The interpersonal skill is an ability to identify and respond a reasonable emotion, act, behaviour, motivation and desire of human being. It is sophisticated and need-skill in routine life. In fact, no one of individu can be isolated from the others. Each others need to others. To operate it, individu must have an specific ability to understand the others. In this context, the study is elaborated through mixed-methodology, the research sucessfully find some points. One of these is that, there is, clear and significant correlation between interpersonal skill and the interest of consumers of Islamic Koperasi, Barakoh of Curup. Keywords: Interpersonal Skill, reasonable Emotion, Motivation, and Interest of Consumers.